Reasons for non-participation in public oncological screening programs in the Italian region Friuli Venezia Giulia. (April 2020) - Valent, F.; Sammartano, F.; Degano, S.; Dellach, C.; Franzo, A.; Gerin, D.; Gnesutta, D.; Mentil, S.; Stel, S.; Pattitoni, C.; Gongolo, F.
Abstract: Objectives: In the Italian region Friuli Venezia Giulia, public screening is offered for cervical cancer, breast cancer, and colorectal cancer. Participation of the target population is lower than 70%. Our aim was to investigate reasons for non-participation. Study design: This is a qualitative survey. Methods: A telephone survey was conducted in 2018 on a random sample of persons not adhering in 2017. Only one question about the reason for non-participation was asked. The answers were transcribed verbatim with no personal identifiers and no additional information. The transcribed anonymous answers were then read and classified into mutually exclusive macrocategories and subcategories. Results: A total of 4456 non-adhering persons were surveyed. Personal practical issues were the most common type of barrier reported in all three screening programs, followed by personal beliefs. Program-related issues were more common in cervical cancer screening than in the others. Almost half of the women not participating in the public breast cancer screening and 40% of those not adhering to the public cervical cancer screening had mammography or Pap test out of the public program. Conclusions: In this region, practitioners should work to overcome practical barriers and discuss personal beliefs. Surveys of non-participants in other geographic areas would be important to adequately inform local policymaking. Highlights: Reasons for non-participation in public cancer screening in this region are unknown. A survey eliciting free responses from 4456 non-participant persons was conducted. Personal reasons (practical issues or beliefs) were the most frequent reasons. Many persons reported to have screening tests out of the public programs. This information is used to improve the quality of the public regional programs.